Clozapine blood level assessment using a point-of-care device: feasibility and reliability - Shiri Kamhi-Nesher; Sharon Taub; Shikma Halimi; Maria Frenkel; Mahmud Azam; Gil Bormant; Helena Isakov; Dikla Radzinsky; Abraham Weizman; Amir Krivoy (SAGE Publishing, 2022)
Background: Therapeutic drug monitoring (TDM) is useful to assess clozapine adherence and optimize treatment. However, analysis of venous blood levels by liquid chromatography tandem mass spectrometry (LC-MS/MS) is often logistically complicated and process time is prolonged. Objective: To assess the feasibility and reliability of a new point-of-care device, (MyCare™ Insite), using capillary blood for clozapine therapeutic monitoring. Methods: Matched venous and capillary blood samples were collected from patients treated with clozapine on a stable dose. Samples were analyzed by LC-MS/MS and MyCare Insite Clozapine Test. Clozapine plasma levels were compared between methods using linear regression model. Both patients and treatment team completed questionnaires about the feasibility of blood sampling. Results: Of the total sample (44 patients, 61% males, mean age 43 ± 12 years), mean daily clozapine dose was 293 ± 134 mg/day. Linear regression model demonstrated high correlation with R 2  = 0.83 ( p  < 0.0001) and mean difference of 26 ± 162 ng/ml. More than 60% of the patients found the clozapine TDM to be important. Most of the participants (58%) favored the capillary sampling and 11% claimed that testing method would affect their adherence to TDM. Moreover, a larger portion (72%) strongly preferred to be tested at the office rather than at the lab. Conclusions: The point-of-care device offers an accessible and satisfactory measurement of clozapine blood levels. Both patients and healthcare providers reported preference for capillary sampling as well as for the in-office TDM procedure. The immediate results provided by the device can facilitate rapid and informed clinical decisions and therefore improve clozapine treatment outcomes.